Are dietary patterns becoming more processed? The effects of different dietary patterns on cognition: A review. Issue 3 (September 2022) - Harriden, Brittany; D'Cunha, Nathan M.; Kellett, Jane; Isbel, Stephen; Panagiotakos, Demosthenes B.; Naumovski, Nenad
Background: Identifying dietary patterns that promote healthy aging has become increasingly important due to changes in food processing and consumption of processed foods. Recently, the effects of these foods and unhealthy dietary patterns on cognitive function have become more widely recognized.Aim: The aim of this review is to discuss the association between various dietary patterns and cognition in older age, while also highlighting growing evidence that ultra processed food (UPF) may negatively impact healthy aging.Methods: We have performed a non-systematic literature review searches in Google Scholar electronic database with pre-defined terms relating to UPF, diet, dietary patterns, cognition and ageing.Results: The most prevalent diets in the literature include the Western, Mediterranean, Dietary Approach to Stop Hypertension (DASH), Mediterranean-DASH Intervention for Neurogenerative Delay (MIND), Japanese, Nordic, and plant-based diets. Based on the findings, higher intakes of fresh fruit and vegetables, wholegrains and oily fish are common components of dietary patterns that are positively associated with better cognitive function. In contrast, the characteristics of a Western style dietary pattern, consisting of high amounts of UPF's, are increasing in many countries even where the staple dietary pattern was identified as healthy (i.e. Japan).Conclusion: The consumption of UPF, classified by the NOVA food classification system as industrially manufactured foods containing high levels of starches, vegetable oils, sugar, emulsifiers, and foods additives, has a negative impact on the overall nutritional quality of individual diets.